High-sensitivity flexible sensing material with adjustable sensing sensitivity and preparation method thereof
Through low-temperature 3D printing technology and silver ion two-step immersion process, a conductive hydrogel with adjustable sensitivity was prepared, which solved the problems of mechanical and electrical sensing performance balance and structure customization of conductive hydrogels, and achieved high performance flexibility Preparation of sensing materials, suitable for smart wearable devices and software robots.
Patent Information
- Application Number
- CN202411527216.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing conductive hydrogels are difficult to balance between mechanical properties and electrical sensing properties, and traditional template casting methods limit structural forms and are difficult to customize applications in specific environments. Too much conductive material during 3D printing affects printability.
Low-temperature 3D printing technology is used to prepare PVA/LS hydrogels. By controlling the angle between the printing path and the stretching direction, and combining with the silver ion two-step immersion process to form a dense conductive layer, achieving both high sensitivity and mechanical properties of the conductive hydrogels.
It realizes flexible sensing materials with adjustable sensing sensitivity, high mechanical strength, excellent conductivity and wide strain response range. They are suitable for intelligent wearable devices and soft robots, and have green, efficient and repeatable preparation processes.
Smart Images

Figure CN119223150A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of high-sensitivity flexible sensing materials, and in particular to a high-sensitivity flexible sensing material with adjustable sensing sensitivity and a preparation method thereof. Background Art
[0002] In recent years, wearable strain sensors have attracted much attention due to their wide applications in electronic skin, soft robots, and health monitoring. As the core component of wearable strain devices, flexible strain sensors can convert mechanical signals into signals such as resistance or capacitance and output them under various external deformation conditions (such as compression, stretching, bending, and torsion), making them have broad development prospects in smart electronic devices. Due to its high flexibility, high ductility, good biocompatibility, adjustable mechanical properties, and easy processing, conductive hydrogels have now become an important research and application direction in the field of flexible sensors.
[0003] Conductive hydrogels are usually composed of a hydrogel matrix and a conductive filler. Although traditional flexible sensors prepared by combining conductive fillers (such as conductive polymers, metals, and carbon-based materials) with a hydrogel matrix have high sensitivity, conductive hydrogels are usually limited in application due to the balance between mechanical properties and electrical sensing properties due to the aggregation of a large amount of conductive fillers in the hydrogel matrix and the weak interface bonding between the conductive fillers and the matrix. In addition, most of these conductive hydrogels are prepared by traditional template casting and other methods. The high dependence on the use of molds limits the structural form of conductive hydrogels, thereby hindering their customized applications in some specific environments. As an effective additive manufacturing technology, 3D printing technology has the advantages of high-precision molding, customized printing structure, and versatility of printing materials. It has been widely used in the preparation of hydrogels with complex structures. However, the large amount of conductive materials introduced into the conductive hydrogel matrix to ensure conductivity usually affects the printability of the matrix material, resulting in incompatibility between the mechanical properties, printability, and electrochemical properties of 3D printed conductive hydrogels. Therefore, there is an urgent need to develop a preparation method for new conductive hydrogels that can effectively balance complex shapes and structures, good mechanical properties, and electrical sensing properties. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a highly sensitive flexible sensing material with adjustable sensing sensitivity, comprising the following steps: Step 1, preparing PVA / LS hydrogel reaction solution: dissolving sodium lignin sulfonate LS and polyvinyl alcohol PVA in a mass ratio of 3%:97% in a mixed solution of dimethyl sulfoxide and deionized water in a volume ratio of 80%:20%, mechanically stirring at 140°C and 400rpm for 2.5h, and cooling to 40°C to obtain a PVA / LS hydrogel reaction solution; Step 2: Using low-temperature 3D printing technology, print at -20°C to form hydrogel matrices with different oriented structures: use 3D modeling software to design the printing path, generate G code and transmit it to the low-temperature 3D printer, the printing temperature is -20°C, keep at -18°C for 24 hours after printing, thaw at room temperature for 2 hours, and soak in deionized water for 4 days; the angle between the printing path and the stretching direction is controllable, preferably 0°, 15°, 30°, 45°, 60°, 75° and 90°; Step 3: Immerse the printed substrate in AgNO3 / PVP solution for 8 hours, and then immerse it in VC / PVP solution for 24 hours for reduction. Silver ions form a dense conductive layer on the surface of the hydrogel to obtain a conductive hydrogel; the concentrations of AgNO3, PVP and VC solutions are 1.0M, 10wt% and 0.08M, respectively.
[0005] A highly sensitive flexible sensing material with adjustable sensing sensitivity is a conductive hydrogel composite material including a PVA / LS hydrogel matrix and a surface silver layer. The hydrogel matrix has an anisotropic orientation structure formed by 3D printing, and the angle between the printing path and the stretching direction controls the sensing sensitivity and strain detection range of the material.
[0006] When the printing path is parallel to the stretching direction, the material has low sensitivity and a strain detection range of 0-20%; when the printing path is perpendicular to the stretching direction, the material has high sensitivity and a strain detection range of 0-55%.
[0007] When the printing path is at an angle of 15°, 30°, 45°, 60°, or 75° to the stretching direction, the material exhibits different sensitivity characteristics, thereby enabling customized regulation of the sensing performance.
[0008] The material has high mechanical strength, high conductivity, high sensitivity and a wide strain response range, and is suitable for strain sensing in the fields of smart wearable devices, electronic skin and soft robots.
[0009] Working principle of the present invention: The hydrogel reaction liquid exhibits shear-thinning behavior at low temperatures, and the viscosity gradually decreases with the increase of shear rate. Below -1.4°C, the reaction liquid has a gelation point. Combining the shear-thinning characteristics and temperature-induced rapid gelation behavior, the reaction liquid has good printability at low temperatures. When the temperature of the low-temperature 3D printer is much lower than -1.4°C, the extruded solution can be quickly solidified and formed to achieve precise patterned deposition.
[0010] Through a two-step immersion process, a dense silver layer is reduced on the surface of the hydrogel. In the first step, the hydrogel is immersed in a mixed solution of AgNO3 / PVP, and a large amount of silver ions penetrate into the hydrogel; in the second step, the hydrogel containing silver ions is immersed in a mixed solution of VC / PVP, and the silver ions are reduced by VC into silver particles and diffused and aggregated on the surface of the hydrogel to form a dense silver layer. The reduction process of the silver layer is mainly affected by the concentration of AgNO3 and VC solutions. As the concentration increases, the nucleation rate of silver ions accelerates, causing the size of silver particles to increase and the distance between particles to decrease, thereby improving the conductivity of the hydrogel. When the concentrations of AgNO3 and VC solutions are 1.0M and 0.08M, respectively, the size of the reduced silver particles is large and uniform, and the adjacent particles are tightly stacked, providing an efficient path for electron movement, making the hydrogel have high conductivity.
[0011] By controlling the angle between the printing path on the upper surface of the hydrogel and the stretching direction, conductive hydrogels with different sensitivities and strain ranges can be prepared. When the printing path is parallel to the stretching direction, the silver layer mainly bears the mechanical load, and cracks are generated during the stretching process and gradually expand, causing the hydrogel resistance to increase slowly, with low sensitivity and a narrow strain range. When the printing path is perpendicular to the stretching direction, the silver layer in the gap between adjacent printing paths mainly bears the load. As the strain increases, more cracks are generated in the silver layer in the gap and expand rapidly, causing the hydrogel resistance to increase rapidly, showing high sensitivity under larger strains. When the printing path is at a certain angle to the stretching direction, the printing path and the silver layer in the gap share the load, showing different sensitivity characteristics.
[0012] Beneficial effects of the present invention: The present invention starts from the perspective of the preparation and structural design of low-temperature 3D printed conductive hydrogels, uses polyvinyl alcohol and lignin sulfonate as matrix materials, and forms a conductive hydrogel matrix with different structural characteristics through low-temperature 3D printing technology. Based on the gelation characteristics of PVA at low temperatures and the reduction process of silver ions on the surface of the hydrogel matrix, the preparation of high-conductivity conductive hydrogels is achieved. By controlling the angle between the printing path and the stretching direction during low-temperature 3D printing, conductive hydrogels with different sensitivities and strain ranges can be achieved. The method for preparing a high-sensitivity flexible sensing material with adjustable sensing sensitivity proposed in the present invention provides a new, high-performance, customizable flexible sensing material solution for the fields of smart wearable devices, soft robots, and human health monitoring.
[0013] The present invention is based on polyvinyl alcohol and lignin sulfonate with good mechanical properties, processability and biocompatibility. By combining low-temperature 3D printing technology with silver ion reduction process, a conductive hydrogel with highly oriented structure and excellent conductive properties is established as the basis of mechanical strength and electrical properties. The gelation characteristics of PVA at low temperature and the two-step immersion reduction process of silver ions on the surface of the hydrogel matrix are used to establish a high conductivity foundation composed of PVA molecular chains and silver particles. Based on the low-temperature 3D printing path design, printing angle control and the conductive mechanism of the conductive hydrogel, a flexible sensing characteristic foundation with adjustable sensitivity is established. At the same time, the low-temperature 3D printing process gives the composite hydrogel a variety of structural characteristics, so that the flexible sensor can achieve customized regulation of sensing performance through structural design. The preparation process based on the combination of low-temperature 3D printing and silver ion reduction involved in the present invention is green, efficient and repeatable. The prepared high-sensitivity flexible sensing material with adjustable sensing sensitivity has high mechanical properties, high electrical conductivity, high sensitivity, wide strain response range and good biocompatibility, and can accurately and real-time detect all-directional strain. The low-temperature 3D printed conductive hydrogel can achieve customized regulation of sensing performance through structural design, meeting the diversified application needs in the fields of smart wearable devices, electronic skin, soft robots, etc., and provides a novel and effective technical solution for the widespread application of high-performance flexible sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a rheological effect diagram of the PVA-LS hydrogel reaction solution of the present invention; Figure 2 This is a real-life rendering of low-temperature 3D printing of the present invention; Figure 3 This is a stress-strain effect diagram of the conductive hydrogel matrix printed at low temperature 3D with different structural forms of the present invention; Figure 4 The low-temperature 3D printed conductive hydrogel object and its microscopic morphology and energy spectrum of the present invention; Figure 5 This is a diagram showing the sensitivity of low-temperature 3D printed conductive hydrogel sensors with different structural forms according to the present invention; Figure 6 This is a graph showing the relative resistance change of the low-temperature 3D printed conductive hydrogel of the present invention after continuous cyclic stretching for 100 times at 55% strain. DETAILED DESCRIPTION
[0015] This embodiment provides a method for preparing a high-sensitivity flexible sensing material with adjustable sensing sensitivity, comprising the following steps: (1) Preparation of matrix material: 1) Sodium lignin sulfonate (LS) and polyvinyl alcohol (PVA) were dissolved in a mixed solution of dimethyl sulfoxide and deionized water in a volume ratio of 80%:20% at a mass ratio of 3%:97%; 2) stirring the mixture for 2.5 hours at 140° C. and 400 rpm, and then cooling the mixture to 40° C. to obtain a PVA-LS reaction solution suitable for low-temperature 3D printing, i.e., a matrix material for the conductive hydrogel; (2) Structural design and preparation of matrix materials: 1) Use drawing software to perform 3D modeling on the printed sample, and convert the 3D model into an STL format file. Use Slic3r software to slice the STL format file to generate G code. Combined with parameters such as printing rate and printing height, the G code is modified into a preset path in a notepad through calculation and transmitted to the low-temperature 3D printer; 2) Load the PVA-LS reaction solution into the extruder of the low-temperature 3D printer, adjust the temperature of the base plate to the preset temperature (-20°C), pre-tighten the extruder containing the reaction solution to ensure that it is continuously extruded during the printing process, and start low-temperature 3D printing; 3) After printing is completed, the cooling system is maintained for 5 minutes. When the temperature of the printer base plate returns to 2°C, the sample is removed and placed in a -18°C refrigerator for 24 hours and then thawed at room temperature for 2 hours. The sample is then immersed in deionized water for 4 days. The deionized water is replaced every 12 hours during the immersion period to obtain a low-temperature 3D printed conductive hydrogel matrix with structural characteristics; (3) Conductive functionalization of structured matrix materials: 1) obtaining a silver nitrate solution (AgNO3) at a concentration of 1.0 M by magnetic stirring, obtaining a polyvinyl pyrrolidone solution (PVP) at a mass fraction of 10 wt.% by magnetic stirring, and obtaining an ascorbic acid solution (VC) at a concentration of 0.08 M by magnetic stirring for later use; 2) Mix equal volumes of ascorbic acid solution and PVP solution to prepare a reducing agent solution, and mix equal volumes of silver nitrate solution and PVP solution to prepare a reducing solution; 3) The low-temperature 3D printed conductive hydrogel matrix with different structural characteristics was immersed in the reducing solution for 8 h, then taken out and placed in the reducing agent solution for 24 h, and then the residual solution was taken out and dried to obtain the conductive hydrogel, completing the conductive functionalization of the structured matrix material.
[0016] Effect analysis: Analyze the rheological effects of PVA-LS hydrogel reaction solution for low-temperature 3D printing, including viscosity, storage modulus, and loss modulus.
[0017] Based on the preparation method, the present invention successfully prepared a conductive hydrogel matrix material reaction liquid. As the shear rate increases, the viscosity of the matrix material reaction liquid gradually decreases, showing typical shear thinning characteristics (such as Figure 1 ), as the temperature decreases, the storage modulus and dissipation modulus of the reaction liquid both increase, and when the temperature is around -1.4 ℃, the storage modulus and dissipation modulus curves intersect with the temperature decrease curves, and there is a liquid-gel transition point, that is, before the liquid-gel transition point, the reaction liquid cannot be solidified and takes on a liquid state; after the transition point, the reaction liquid undergoes cross-linking and solidification to take on a colloidal state. When the temperature is -10 ℃, the storage modulus of the reaction liquid is much larger than the dissipation modulus, which indicates that at temperatures of -10 ℃ or lower, the cross-linking and curing effect of the reaction liquid is better, which ensures that the bottom printing material can carry more layers of printing material without collapse and deformation, so that the conductive hydrogel matrix can maintain a good printing structure during the printing process. When the printer temperature is -20 ℃, the printing path of the sample is clear, without collapse, and is completely solidified (such as Figure 2 ). Based on the above analysis, it can be seen that the conductive hydrogel reaction solution has the feasibility of low-temperature 3D printing.
[0018] The present invention compiles the G code to obtain structural forms in which the angles of two adjacent layers of printing path structures change to 15°, 30°, 45°, 60°, 75°, and 90°. The tensile strengths of the conductive hydrogel matrices in which the angles of two adjacent layers change to 15°, 30°, 45°, 60°, 75°, and 90° are 0.51 MPa, 0.56 MPa, 0.45 MPa, 0.45 MPa, 0.33 MPa, and 0.34 MPa, respectively; and the elongations at break are 247%, 288%, 215%, 235%, 195%, and 152%, respectively (e.g. Figure 3 ). Compared with the structure with an angle of 0°, the tensile strength and elongation at break of the conductive hydrogel matrix with the angles of two adjacent layers changing to 15°, 30°, 45° and 60° are significantly improved. When the angles of two adjacent layers change to 75° and 90°, the tensile properties of the low-temperature 3D printed conductive hydrogel matrix are poor. This is because in their printing path structure, there are many layers with excessive deflection angles from the stretching direction, which makes it difficult to fully bear the tensile load, resulting in a decrease in their tensile properties. Different structural forms provide different mechanical strength options for the conductive hydrogel matrix and provide a good mechanical strength foundation for its sensing function application.
[0019] After the conductive process, due to Ag +After being reduced to elemental silver by VC, the surface color of the hydrogel sample turned white. After the low-temperature 3D printed conductive hydrogel matrix was functionalized, its printing path structure was still preserved, which shows that the conductive process has little effect on the molding accuracy of the low-temperature 3D printed conductive hydrogel. The microstructure and element distribution of the cross-section of the conductive hydrogel show that the surface of the sample is almost completely covered by the reduced silver layer, and there is almost no elemental silver (such as Figure 4 ), providing a functional basis for high conductivity and sensing sensitivity.
[0020] As the tensile strain gradually increases, the relative resistance changes of the conductive hydrogels with different upper surface printing path structures all increase (e.g. Figure 5 ). The increasing trend of relative resistance change of low-temperature 3D printed conductive hydrogels with different upper surface printing path structures is significantly different, which shows that it is feasible to change the printing path structure through low-temperature 3D printing process on its sensing performance without changing the base material ratio and conductive process parameters. Different sensing performances can be achieved by changing the upper surface printing path structure of low-temperature 3D printed conductive hydrogels without changing the material ratio and conductive process. For example, the 0° conductive hydrogel with the best linearity has an effective sensing strain range of 0-20% and a sensitivity of 27.18, and has a high sensitivity characteristic for detecting small strains; while the 90° conductive hydrogel has the widest effective sensing strain range of 0-55%, and has a higher relative resistance change under larger strains, which is suitable for monitoring scenarios with larger deformations. Therefore, in the practical application of low-temperature 3D printed conductive hydrogels, the printing path structure can be changed to meet different working conditions and achieve more accurate sensing functions.
Claims
1. A method for preparing a highly sensitive flexible sensing material with adjustable sensing sensitivity, characterized in that: The following steps are involved: Step 1, preparing PVA / LS hydrogel reaction solution: dissolving sodium lignin sulfonate LS and polyvinyl alcohol PVA in a mass ratio of 3%:97% in a mixed solution of dimethyl sulfoxide and deionized water in a volume ratio of 80%:20%, mechanically stirring at 140°C and 400rpm for 2.5h, and cooling to 40°C to obtain a PVA / LS hydrogel reaction solution; Step 2: Using low-temperature 3D printing technology, print at -20°C to form hydrogel matrices with different oriented structures: use 3D modeling software to design the printing path, generate G code and transmit it to the low-temperature 3D printer, the printing temperature is -20°C, keep at -18°C for 24 hours after printing, thaw at room temperature for 2 hours, and soak in deionized water for 4 days; the angle between the printing path and the stretching direction is controllable, preferably 0°, 15°, 30°, 45°, 60°, 75° and 90°; Step 3: Immerse the printed substrate in AgNO3 / PVP solution for 8 hours, and then immerse it in VC / PVP solution for 24 hours for reduction. Silver ions form a dense conductive layer on the surface of the hydrogel to obtain a conductive hydrogel; the concentrations of AgNO3, PVP and VC solutions are 1.0M, 10wt% and 0.08M, respectively.
2. A highly sensitive flexible sensing material with adjustable sensing sensitivity prepared by the method for preparing a highly sensitive flexible sensing material with adjustable sensing sensitivity according to claim 1, characterized in that: A highly sensitive flexible sensing material with adjustable sensing sensitivity is a conductive hydrogel composite material including a PVA / LS hydrogel matrix and a surface silver layer. The hydrogel matrix has an anisotropic orientation structure formed by 3D printing, and the angle between the printing path and the stretching direction controls the sensing sensitivity and strain detection range of the material.
3. The high-sensitivity flexible sensing material with adjustable sensing sensitivity according to claim 2, characterized in that: When the printing path is parallel to the stretching direction, the material has low sensitivity and a strain detection range of 0-20%; when the printing path is perpendicular to the stretching direction, the material has high sensitivity and a strain detection range of 0-55%.
4. The high-sensitivity flexible sensing material with adjustable sensing sensitivity according to claim 3, characterized in that: When the printing path is at an angle of 15°, 30°, 45°, 60°, or 75° to the stretching direction, the material exhibits different sensitivity characteristics, thereby enabling customized regulation of the sensing performance.
5. A high-sensitivity flexible sensing material with adjustable sensing sensitivity according to any one of claims 2 to 4, characterized in that: The material has high mechanical strength, high conductivity, high sensitivity and a wide strain response range, and is suitable for strain sensing in the fields of smart wearable devices, electronic skin and soft robots.
Citation Information
Patent Citations
Nanofiber film fabric type flexible capacitive sensor and preparation method thereof
CN115979314A
High-sensitivity conductive hydrogel low-temperature 3D printing device and preparation method
CN116039073A
